Change or continuity? The impact of New Labour's modernisation programme on grassroots football within Hampshire. Issue 12 (2nd December 2022) - Bailey, Andrew
Abstract: During their time in government, New Labour sought to modernise and professionalise public services and this included the voluntary sector in sport. This paper explores to what extent grassroots football within Hampshire has changed in response to the modernisation process. Grassroots football has traditionally been dependent on the time and efforts of volunteers, contributing to an amateur-voluntary culture. Six semi-structured interviews, with members of the grassroots voluntary workforce, suggest that more needs to be done in diversifying the local workforce. Moreover, modernisation through technology and the FA Charter Standard Programme have benefitted local football and have generally been well received. However, there is a tension between the amateur-voluntary traditions of grassroots football; and the modernised, professionalised, inclusive society which New Labour developed through their modernisation agenda. Thus, this research demonstrates that modernisation is not a time limited process, rather an ongoing process which continues beyond New Labour's time in office.